Intracranial Subdural Hematoma Following Neuraxial Anesthesia in the Obstetric Population: A Literature Review With Analysis of 56 Reported Cases. Issue 4 (December 2016) - Cuypers, V.; Van de Velde, M.; Devroe, S.
Abstract : ( Int J Obstet Anesth . 2016;25:58–65) Intracranial subdural hematoma is a rare but life-threatening complication of dural puncture that can occur following epidural or spinal anaesthesia. Severe neurological sequelae can be avoided, however, if early diagnosis is made and prompt treatment initiated. The objective of this study was to identify cases of intracranial subdural hematoma following neuraxial anesthesia in obstetric patients, summarize presentation and outcomes and identify risk factors.